Financial Strategy for Shanghai Electric Group Company Limited - Yanan, Wang; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2019)
Abstract. In recent years, the environment of power manufacturing industry has become severe. As the price of steel raw materials in the international market rises year by year and China's electricity demand tends to be saturated, power equipment manufacturing companies face enormous challenges. While exploring new markets, efforts to improve financial management and reduce costs have become the goals that power industry companies need to achieve. How to implement a good finance strategy is an urgent need for power equipment manufacturing companies. This research aims to analyze and measure the financial health conditions of Shanghai Electric Group Company limited for period 2013-2017, as an example for case analysis. The research concerns about five classification of ratios measurement that includes liquidity, solvability, activity, profitability and growth capacity ratios, which makes analysis with directly competitors, namely Dongfang Electric Company, and China XD Electric Company. In addition, this research also uses DuPont analysis, Porter's five-force analysis and SWOT analysis methods to deeply analyze the financial status and market competitiveness of Shanghai Electric Group Company Limited. Based on the analysis, this final project concludes that in order to maintain a leading position in power equipment manufacturing industry, Shanghai Electric needs to improve the effective utilization of funds, strengthen the management of accounts receivable, enhance its comprehensive budget management, increase financial risk awareness, establish diversified investment management and make reasonable market adjustment.Key Words: Shanghai Electric, Corporate Strategy, DuPont